2012
DOI: 10.3758/s13423-012-0242-x
|View full text |Cite
|
Sign up to set email alerts
|

Music-reading expertise alters visual spatial resolution for musical notation

Abstract: Crowding occurs when the perception of a suprathreshold target is impaired by nearby distractors, reflecting a fundamental limitation on visual spatial resolution. It is likely that crowding limits music reading, as each musical note is crowded by adjacent notes and by the five-line staff, similar to word reading, in which letter recognition is reduced by crowding from adjacent letters. Here, we tested the hypothesis that, with extensive experience, music-reading experts have acquired visual skills such that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…performed the perceptual fluency task to quantify individual music reading ability (Wong & Gauthier, 2010a; 2010b; 2012). The task used a sequential matching paradigm with music sequences containing four notes each.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…performed the perceptual fluency task to quantify individual music reading ability (Wong & Gauthier, 2010a; 2010b; 2012). The task used a sequential matching paradigm with music sequences containing four notes each.…”
Section: Methodsmentioning
confidence: 99%
“…Although the C1 is typically measured with stimuli presented in the upper or lower visual fields (Clark et al, 1995; Jeffreys & Axford, 1972; Kelly et al, 2008; Pourtois et al, 2004; Proverbio & Adorni, 2009; Rauss et al, 2011), it can also be measured with foveally presented stimuli as in the current design (Foxe et al, 2008; Giard & Peronnet, 1999). We chose to present stimuli at the fovea because parafoveal presentation would both depart from the fMRI study in which we observed V1 activation in music reading experts (Wong & Gauthier, 2010a) and could produce large behavioral differences in novice vs. expert performance (Wong & Gauthier, 2012) that could complicate the interpretation of the results (e.g., more small eye movements toward the stimuli in one group). We focused on the early part of the C1 because, in this time window, the activity is too early to be explained by extrastriate activity in the next P1 component (onset around 60-90ms) or in higher-level visual cortex (Bao et al, 2010; Clark et al, 1995; Clark & Hillyard, 1996; Foxe et al, 2008; Luck, 2005; Martinez et al, 1999), and most of the activated cells are in the LGN and V1 during this latency (Schmolesky et al, 1998).…”
mentioning
confidence: 99%
“…Musicians exhibit enhanced perceptual abilities for musical stimuli, as reflected for instance by a reduction of perceptual crowding, selectively for musical stimuli, in proportion to music reading fluency (Wong and Gauthier, 2012). Another facet of expertise may be the encoding of frequent combinations of notes, such as rhythmic, melodic, or chord patterns, as a single object.…”
Section: Correlates Of Musical Expertisementioning
confidence: 99%
“…Crowding effects are smaller for letters than for symbols, presumably due to the modified size of the crowding region for letters in words during reading acquisition (Grainger et al, 2010). Music-reading experts show a smaller crowding effect than novices when they are asked to identify the location (on a line or on a space) of a crowded music note, but not when they are asked to identify the location of the gap of a crowded Landolt C (Y. K. Wong & Gauthier, 2012). Crowding is smaller when an upright target face is surrounded by inverted compared to upright faces, presumably due to the loss of our normal proficiency at face perception (and thus less interference) when faces are inverted (Farzin et al, 2009;Louie et al, 2007).…”
Section: Introductionmentioning
confidence: 99%